Pengaruh Pemberian Kombinasi Jenis dan Dosis Pupuk Kandang terhadap pH, N-Total, Serapan-N, serta Hasil Tanaman Pakchoi (Brassica chinensis L.) pada Fluventic Eutrudepts - Dewi Septian Pujiningsih; Anni Yuniarti; Apong Sandrawati (Fakultas Pertanian Universitas Padjadjaran, 2019)
ABSTRACTThe effect of the combination types and dosages of manure on soil reaction, N-total, N-uptake, and yield of pakchoi (Brassica chinensis L.) on fluventics eutrudeptsThis research was conducted to determine the effect of the combination types and dosages of manure on soil reaction, N-total, N-uptake, and yield of pakchoi (Brassica chinensis L.) on Fluventics Eutrudepts. The study was conducted from April to Agustus 2010 in the research station Greenhouse Faculty of Agriculture, Universitas Padjadjaran, Jatinangor Sumedang, West Java, elevated at 700 meters above sea level. The experimental design used was Randomized Block Design (RBD) with eleven treatments and three replications, consisted of without fertilizer (control); one dose of inorganic fertilizer and chicken manure 25 g/polybag; 0.75 dose of inorganic fertilizer and chicken manure 37.5 g/polybag; 0.5 dose of inorganic fertilizer and chicken manure 50 g/polybag; 0.25 dose of inorganic fertilizer and chicken manure 62.5 g/polybag; no inorganic fertilizer and chicken manure 75 g/polybag; one dose of inorganic fertilizer and sheep manure 25 g/polybag; 0.75 dose of inorganic fertilizer and sheep manure 37.5 g/polybag; 0.5 dose of inorganic fertilizer and sheep manure 50 g/polybag; 0.25 dose of inorganic fertilizer and sheep manure 62.5 g/polybag; no inorganic fertilizer and sheep manure 75 g/polybag. The results showed that significant effects of soil reaction, N-total, N-uptake, and yield of pakchoi from combination of types and dosages of manure. Treatment of 0.25 dose of inorganic fertilizer and chicken manure 62.5 g/polybag increased yields of pakchoi became 76.77 g.Keywords: Manure combination, Pakchoi, Fluventics EutrudeptsABSTRAKPercobaan ini dilakukan untuk mengetahui pengaruh pemberian kombinasi jenis dan dosis pupuk kandang terhadap pH tanah, N-total, serapan-N, dan hasil tanaman pakchoi (Brassica chinensis L.)pada Fluventics Eutrudepts. Percobaan ini dilaksanakan pada bulan April sampai dengan Agustus 2010 di Rumah kaca kebun Percobaan Fakultas Pertanian Universitas Padjadjaran, Jatinangor, Kabupaten Sumedang, Jawa Barat, dengan ketinggian tempat 700 meter di atas permukaan laut. Rancangan percobaan yang digunakan adalah Rancangan Acak Kelompok (RAK) faktor tunggal dengan sebelas perlakuan dan tiga ulangan, yaitu yang terdiri dari tanpa pupuk (Kontrol); 1 dosis pupuk anorganik dan Pupuk kandang ayam 25 g/polibeg; 0,75 dosis pupuk anorganik dan Pupuk kandang ayam 37,5 g/polibeg; 0,5 dosis pupuk anorganik dan Pupuk kandang ayam 50 g/polibeg; 0,25 dosis pupuk anorganik dan Pupuk kandang ayam 62,5 g/polibeg; tanpa pupuk anorganik dan pupuk kandang ayam 75 g/polibeg; 1 dosis pupuk anorganik dan pupuk kandang domba 25 g/polibeg; 0,75 dosis pupuk anorganik dan Pupuk kandang domba 37,5 g/polibeg; 0,5 dosis pupuk anorganik dan pupuk kandang domba 50 g/polibeg; 0,25 dosis pupuk anorganik dan pupuk kandang domba 62,5 g/polibeg; dan tanpa pupuk anorganik dan pupuk kandang domba 75 g/polibeg. Hasil penelitian menunjukkan terdapat pengaruh terhadap pH, N-total, serapan N, dan hasil tanaman anorganik dan pupuk kandang ayam 62,5 g/polibeg dapat meningkatkan hasil tanaman pakchoi menjadi 76,77 g.Kata Kunci: Kombinasi pupuk kandang, pakchoi, Fluventics Eutrudepts